HSK21542 in patients with postoperative pain: two phase 3, multicentre, double-blind, randomized, controlled trials - Yinbo Zhong; Younian Xu; Qian Lei; Mengchang Yang; Saiying Wang; Xiaoling Hu; Haihui Xie; Yalan Li; Zhong Qin; Zhengfeng Gu; Jiaqiang Zhang; Yuexin Wang; et al. (Nature Communications)
Abstract HSK21542, a peripherally restricted kappa opioid receptor agonist, was evaluated for efficacy and safety in patients with postoperative pain following abdominal surgery. This was assessed in two phase 3, multicentre, randomized, double-blind, controlled trials (HSK21542-301 [ClinicalTrials.gov identifier, NCT04738357] and HSK21542-303 [ClinicalTrials.gov identifier, NCT05390905]) in China. HSK21542-301 was a dual-arm study comparing HSK21542 1.0 μg/kg with placebo, while HSK21542-303 involved three arms comparing HSK21542 1.0 μg/kg with tramadol 50 mg/dose and placebo. All treatments were administered intravenously. The primary endpoint was the time-weighted summed pain intensity differences over 24 h (SPID0-24 h). Both HSK21542-301 (least squares [LS] mean [± standard error], −39.1 [1.88] vs −27.4 [1.89]; P < 0.001) and HSK21542-303 (−64.0 [2.25] vs −45.9 [2.25]; P < 0.001) demonstrated superiority of HSK21542 over placebo in terms of SPID0-24 h, while HSK21542-303 showed non-inferiority to tramadol (LS mean difference, −1.1; 95% confidence interval, −7.4 to 5.1; P < 0.001). Furthermore, HSK21542 had a comparable safety profile to placebo, inducing fewer gastrointestinal adverse events compared with tramadol. Grade ≥3 treatment-emergent adverse events occurred in eight (5.9%) and three (2.3%) patients in the HSK21542 arm of HSK21542-301 and HSK21542-303, respectively. In conclusion, HSK21542 showed potent analgesic effect and was well tolerated in patients who underwent abdominal surgery and experienced postoperative pain.